Genome assembly and functional predation analysis of novel Bdellovibrio isolates from human gut microbiota - Romero-Rivera, Mario; Fernández-de-Bobadilla, Miguel D.; Beltrán, María; del Campo, Rosa; Avendaño-Ortiz, José; Herencias, Cristina (Frontiers in Microbiology, 2026)
IntroductionPredatory bacteria of the Bdellovibrio and like organisms (BALOs) have long been postulated as living antimicrobials, yet their occurrence and ecological roles within human-associated microbiota have remained uncertain due to the absence of culturable human-derived isolates. Here, we report the first successful isolation and comprehensive characterization of viable Bdellovibrio bacteriovorus from human fecal samples.MethodsTargeted enrichment was applied to five pooled fecal samples to facilitate predator recovery. We performed whole-genome sequencing on the isolates and conducted comparative genomics across 162 publicly available Bdellovibrio genomes. Additionally, pangenome analysis of 22 high-quality genomes and phenotypic assays against clinical pathogens were conducted to assess genomic diversity, prey specificity, and biosafety profiles.ResultsDespite extremely low natural abundance, targeted enrichment recovered predators in two of five pooled samples, which produced characteristic lytic plaques. Sequencing revealed >99% average nucleotide identity to reference strain HD100 with only 26 core single-nucleotide polymorphisms across both isolates, indicating minimal divergence between human-associated and environmental lineages. Comparative genomics showed that only 10.4% of public genomes fulfill criteria for B. bacteriovorus sensu stricto. Pangenome analysis revealed a stable, highly conserved core (~2,500–2,650 genes) and an expanding accessory genome. Phenotypically, the human-derived isolates displayed narrower prey ranges concentrated on Pseudomonas spp., including multidrug-resistant clinical strains, and no acquired virulence factors were detected.DiscussionCollectively, these findings suggest predation in the human gut and that viable Bdellovibrio could be natural, genomically conserved members of the intestinal ecosystem. This work advances a testable keystone-predator framework for human microbiome ecology and opens an ecologically informed therapeutic pathway in which human-associated Bdellovibrio may help control multidrug-resistant pathogens while supporting microbiota homeostasis.